(untitled) (Acta Scientiarum. Health Sciences, 2016)
The aim was to assess whether the low level laser therapy (LLLT), 660 nm, can lower the effect of injectable anesthetics in rats. Wistar rats (n = 20) were used in two steps: 1) grip strength test and measuring the anesthesia time for control (G1A) and irradiated (G1AL) groups; 2) after 15 days, rats received new anesthesia injection and were evaluated for nociception (G2A - control; G2AL - laser). Anesthesia was induced by ketamine hydrochloride (75 mg kg-1) and xylazine (10 mg kg-1), by intraperitoneal injection, according to the body weight. LLLT used was 660 nm at four sites along the right hind limb. Anesthesia time was shorter for the G1AL (p = 0.0031). There were significant differences between pre- and post-intervention in the grip strength test (p < 0.001), but no differences were detected between groups (p = 0.459). For nociception, G2AL achieved higher values than G2A (p = 0.019 and p = 0.032), and also for the comparison between pre-injury values with the following values (p < 0.001) although no significant difference was found between 10 and 60 minutes (p > 0.05). It can be concluded that the LLLT caused no significant reduction on the effect of anesthesia.